Profitability Enhancement Strategy Through Capacity Expansion and Market Export Diversification (Case Study: Acquisition of Thang Long Cement Vietnam by PT Semen Indonesia Tbk - Putri, Anandita Ade; Siahaan, Uke MMP (The Indonesian Journal of Business Administration, 2014)
Abstract - Cement industry is expected to be grow respectively high due to demand for house building and infrastructure needs. Indonesia and Vietnam, as part of Southeast Asia region, are facing different kind of market condition. PT Semen Indonesia Tbk is Indonesia’s top leader in cement industry, who had invested major investment by acquiring major shares ownership of Thang Long Cement Company Vietnam, back in late 2012. This acquisition strategy was intended to enhance profitability and reach Southeasr Asia market. One year after the acquisition happened, this strategy needs to be analyzed whether it already goes perfectly as what expected or needed some improvement regarding company’s profitability growth. By doing Discounted Cash Flow valuation with three different scenarios; first is when each companies stand alone independently (before acquisition), second scenario is PT Semen Indonesia Tbk acquired Thang Long Cement Vietnam (current condition) and third scenario is post-acquisition analysis after acquisition with proposed strategy on capacity expansion and market export diversification; and also Relative Valuation as comparable analysis with another cement companies, such as Indocement Tunggal Prakarsa and Holcim Indonesia. This final project suggested Thang Long Cement Vietnam to expand capacity from 2,3 mt/year to 4 mt/year, to improve sales and also doing more exporting market. Vietnam’s cement industry is having excess supply, that’s why exporting cement products to another country is important. Indonesia can also fulfill its massive demand of cement from Vietnamese cement product, which it related to PT Semen Indonesia revenue and inventory availability. Thang Long Cement Vietnam was acquired undervalued with price of US$157million, but it doesn’t mean the company suffered loss from the transactions. PT Semen Indonesia Tbk did major improvement on management structure, business process and debt refinancing for Thang Long Cement Companies. Due diligence was also done before choosing Thang Long Cement Companies as the targetted company, based on its financial ratio analysis which also calculated in this final project. Generally, this acquisition between PT Semen Indonesia and Thang Long Cement Vietnam is a right decision and still possible to reach optimality in profitability enhancement through proposed strategy in expansion and market export diversification. Both companies also proved having synergistic relationship on this acquisition.Keywords: Semen Indonesia, Thang Long Cement Vietnam, acquisition, profitability, expansion, market export, financial analysis